The Gendered Impact of In-State Tuition Policies on Undocumented Immigrants' College Enrollment, Graduation, and Employment - Susan L. Averett; Cynthia Bansak; Grace Condon; Eva Dziadula (Institute of Labor Economics (IZA), 2023)
Since 2001, about half of U.S. states have extended in-state college tuition benefits to undocumented immigrants. Some states have also offered financial aid, while others became more restrictive. Building on previous research, we exploit these additional policies, control for Deferred Action for Childhood Arrivals (DACA), and estimate the impact of in-state tuition on college enrollment, college graduation, employment, and self-employment. In our pooled sample of likely undocumented Hispanic youth, we corroborate the most recent work by also finding no effect of in-state tuition policies on enrollment. However, unlike previous studies, we allow for heterogeneity by gender and marital status and we demonstrate that there are gendered impacts. Women do not respond to in-state tuition. In contrast, men do enroll in college at higher rates regardless of financial aid opportunities. In-state tuition access results in higher graduation rates for women, driven by single women, but not for men. In terms of labor market attachment for undocumented youth, we find single women are more likely to work and single men to be self-employed when eligible for in-state tuition. Thus, the in-state policy motivates single women to complete their degrees and work. If policymakers intend to have a broader impact and target a more inclusive group of undocumented youth, including men, they should consider enhancing their opportunities in formal labor markets after college graduation. In support of this argument, we document a higher graduation and employment rates, along with lower self-employment rates, among DACA-eligible youth who have legal access to formal employment.
Keywords: J15; I22; 330; in-state tuition; undocumented immigrants